2012
DOI: 10.1016/j.ihj.2012.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Different transcatheter strategies for aortic coarctation associated with patent ductus arteriosus

Abstract: In coarctation with patent ductus arteriosus associated with good sized aortic isthmus, closure of duct with duct occluder device and balloon aortoplasty would correct the lesions. If there is isthmic hypoplasia, device closure of the duct and stenting of the coarctation is needed. Covered stent is a reasonable alternative only in presence of non dilated descending aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In addition, other early postoperative complications such as paradoxical hypertension, aortic dissection, left recurrent laryngeal nerve paralysis, phrenic nerve injury, and subclavian steal are still important [ 11 ]. Transcatheter closure of moderate-to-large ducts with occluder devices has been widely practiced in recent years [ 4 ]. Treatment of CoA associated with PDA depends on patient's age, features of coarcted segment, and the size of the duct [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, other early postoperative complications such as paradoxical hypertension, aortic dissection, left recurrent laryngeal nerve paralysis, phrenic nerve injury, and subclavian steal are still important [ 11 ]. Transcatheter closure of moderate-to-large ducts with occluder devices has been widely practiced in recent years [ 4 ]. Treatment of CoA associated with PDA depends on patient's age, features of coarcted segment, and the size of the duct [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter closure of moderate-to-large ducts with occluder devices has been widely practiced in recent years [ 4 ]. Treatment of CoA associated with PDA depends on patient's age, features of coarcted segment, and the size of the duct [ 4 ]. Patients with small sized common femoral artery are not suitable candidates for endovascular interventions with big sized endovascular stent grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, there have been few reported cases of simultaneous management of PDA and coarctation of aorta in the literature with similar context [1]- [5]. Celebi et al have reported a case of simultaneous management of coarctation of aorta and PDA with balloon angioplasty and PDA coil embolization [1].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several types of coils and devices are used for PDA closure [2]. There are reports of both the lesions being treated successfully in cardiac catheterization laboratory, either simultaneously [1]- [5] in a single sitting or sequentially [5]- [8] in two different sittings. Here, we present a case of simultaneous management of coexisting aortic coarctation and patent ductus arteriosus in a young boy.…”
Section: Introductionmentioning
confidence: 99%